Evaluasi Pengelolaan Berkas Rekam Medis Untuk Pencegahan Misfile di Rumah Sakit Umum Daerah Kabupaten Buton - Mega Ermasari Muzuh; Wa Ode Harlisa (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Misfile is an error in the placement of medical record documents. Misfile events will have an impact on patient care that is longer and can result in a decrease in the quality of health services in hospitals effectively and efficiently. The purpose of this study was to determine the management of medical record files so that medical record file misfiles do not occur at the Buton District General Hospital in 2019 based on 5 M (Man, Material, Mechine, Money, Method). The design of this research is descriptive qualitative. The results of the study found that the incidence of misfile in the Buton District Hospital was caused by the man and money factors. The conclusion of this study is that the cause of misfiled events at the Buton district hospital is because the medical record officer does not have a medical record education background and has never attended medical record training, as well as a small amount of funds for the medical record room so that there are still many shortcomings in the medical record unit, especially the filing section.